2007
DOI: 10.1111/j.1752-1688.2007.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Relative Efficiency of Brazilian Publicly and Privately Owned Water Utilities: A Stochastic Cost Frontier Approach1

Abstract: This paper assesses cost efficiencies of Brazilian public and private companies of water supply. To measure the efficiency, we used a stochastic frontier model derived from the translog family -a specification similar to a Cobb-Douglas including a quadratic term in log output. The model parameters are estimated by maximum likelihood using Brazilian data for the year 2002. Statistical inference leads to the conclusion that there is no evidence that private firms and public firms are significantly different in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 22 publications
2
14
0
3
Order By: Relevance
“…His study also showed that privately-equity firms were highly efficient. On the contrary, da Silva e Souza et al [29] estimated the relative efficiency of Brazilian publicly and private owned water utilities by implementing a stochastic cost frontier approach but no significant differences emerged between the two types of operators. Seroa da Mota and Moreira [30] also found that ownership has no effect on efficiency gains in the provision of local municipal services, even though, after privatization, the local private operators have moved faster than public ones towards the efficient frontier.…”
Section: Private Vs Public Ownership And/or Management Of Water Provmentioning
confidence: 99%
“…His study also showed that privately-equity firms were highly efficient. On the contrary, da Silva e Souza et al [29] estimated the relative efficiency of Brazilian publicly and private owned water utilities by implementing a stochastic cost frontier approach but no significant differences emerged between the two types of operators. Seroa da Mota and Moreira [30] also found that ownership has no effect on efficiency gains in the provision of local municipal services, even though, after privatization, the local private operators have moved faster than public ones towards the efficient frontier.…”
Section: Private Vs Public Ownership And/or Management Of Water Provmentioning
confidence: 99%
“…As shown in Table 1, these include both water or sewerage (wastewater) only companies (Norman and Stoker 1991, Thanassoulis 2000, Woodbury and Dollery 2004Byrnes et al 2009) and water and sewerage companies (Thanassoulis 2002, Tupper and Resende 2004, Erbetta and Cave 2006 and both public and private utilities (Lambert et al 1993, Kirkpatrick et al 2006, Da Silva e Souza et al 2007, Munisamy 2010. As shown in Table 1, these include both water or sewerage (wastewater) only companies (Norman and Stoker 1991, Thanassoulis 2000, Woodbury and Dollery 2004Byrnes et al 2009) and water and sewerage companies (Thanassoulis 2002, Tupper and Resende 2004, Erbetta and Cave 2006 and both public and private utilities (Lambert et al 1993, Kirkpatrick et al 2006, Da Silva e Souza et al 2007, Munisamy 2010.…”
Section: Scope and Outcomes Of Past Studiesmentioning
confidence: 99%
“…Coelli and Walding (2005) and Bhatttacharyya et al (1994) also exclude the costs of fixed capital. For example, Aubert and Reynaud (2005) and Da Silva e Souza et al (2007) specify the input prices and quantities of labour and electricity; Filippini et al (2008) adds materials;and Fraquelli and Moiso (2005) further include the price and quantities of services and capital. For example, Aubert and Reynaud (2005) and Da Silva e Souza et al (2007) specify the input prices and quantities of labour and electricity; Filippini et al (2008) adds materials;and Fraquelli and Moiso (2005) further include the price and quantities of services and capital.…”
Section: Specification Of Inputs and Outputsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feigenbaum and Teeples (1983), Byrnes et al. (1986), Teeples and Glyer (1987), Houtsma (2003); see also for Spain –Garcia‐Sanchez (2006) and Brazil –da Silva e Souza et al. (2007).…”
mentioning
confidence: 99%